أنماط الإضمار في مقالات صحيفة (الاتحاد) - حسن, أ.م.د.كورديا أحمد; فتاح, شياو جبار (Sulaimani Journal for Humanities, 2023)
Through this research, we seek to shed light on the implicit patterns and methods that were traced by (Al-Ittihad) newspaper, which is a political weekly that lasted more than two and a half decades, by examining it through its political articles that were written by the owners of Kurdish opinions and views at the time, in an effort to develop what the Kurdish people adopted. Through his uprising, parliament and institutions. We have considered the crystallized political ideas that serve this sphere regionally and internationally, observing the deliberative structures and the pillars of inclusion in it, through three main demands, namely: the obligation, the principle of cooperation, and the context. The pronoun is an important element, especially if the speech bears more than one meaning, and obtains more than one sign.